DIGITAL STRATEGY OF POLITICAL COMMUNICATION MEDIA ON SOCIAL MEDIA - E Rizky Wulandari; M. Nashoihul Ibad (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Abstract This research study is used to find out the political communication strategies used in today's media era with the presence of digital media. Mastery of digital media is the latest technology needed in changing society. Social media is becoming a media that is more used by legislative candidates because it has a targeted impact on prospective voters who are desired by political candidates. Communication strategies carried out to successfully communicate politics require several related strategies, either directly or using approaches through social media. This research method uses qualitative approaches and case study methods.